Pengembangan Teknologi ERP Untuk Modul Human Resource Management, Marketing and Sales Studi Kasus UD. Mitra Kobes Rattan - Zain Khairullah; Minarni Minarni (Forum Kerjasama Pendidikan Tinggi (FKPT), 2020)
UD. Mitra Kobes Rattan is a trading business engaged in the processing of semi-finished rattan. The process of collecting employee data, attendance, payroll is done by taking notes in books and calculating using a calculator. Likewise, marketing of this product is still carried out by word of mouth from the surrounding community, there is no media to promote products and manage product sales data. In today's era, ERP technology, namely Enterprise Resource Planning, is very helpful for developing and advancing various agencies and companies. To solve problems that exist at UD. Mitra Kobes Rattan created an ERP system for the Human Resource Management module to help manage employee data. The Marketing and sales module is used to promote products and manage product sales data. This system was built using the PHP programming language and MySQL database. This system can be accessed online both from the admin side and the user in the form of people who can place orders and purchase products. Marketing techniques are also greatly helped by including social media links on the product sales web so that the marketing scope is wider